Campur kode dan alih kode dalam Proses Pembelajaran di SMP Negeri 1 Terentang - Suharyani, Suharyani; Patriantoro, Patriantoro; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to describe the forms of code mixing and code switching that occur in the learning process at SMP Negeri 1 Terentang. Analyze data related to forms of code mixing and code switching, types of code mixing and code switching, and analyze the factors that influence them. The method used in this research is a qualitative descriptive method. The data used in this research are speech uttered by teachers and students in the form of words, phrases and sentences related to code mixing and code switching. Data collection techniques include observation, recording techniques and note-taking techniques. The technique for testing the validity of the data is the technique of diligent observation and adequacy of references. This research produced a form of code mixing in 52 conversations, resulting in 77 code mixing data, with details of 45 word form data, 30 phrase form data, and 2 clause form data; 67 code mixed data into (Inner Code Mixing), 7 code mixed data out (Outer Code Mixing) and 3 mixed code mixed data(Hybrid Code Mixing); The code switching data contained in 10 conversations obtained 53 data in the form of code switching, with details of 7 data in the form of words and 46 data in the form of sentences. The 10 conversations were divided into two, namely 2 permanent code switches and 8 temporary code switches. All code switching data obtained includes inward code switching (Internal Code Switching). Social factors that influence code mixing and code switching are divided into four, namely social status, education level, age, and gender. There are five factors that influence the use of code mixing, including; (1) the speaker's personal and conversation factors 29 data, (2) the presence of a third speaker 2 data, (3) the interlocutor factor 3 data, (4) the prestige factor 7 data, (5) the subject matter factor 11 data; The factors that influence the use of code switching are 2 speaker factor data, 3 interlocutor factor data, and 5 conversation topic and situation factor data.